2021
DOI: 10.2478/bjmg-2021-0018
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Venous Thromboembolism in Sudanese Pregnant Women

Abstract: Venous thromboembolism (VTE) is one of the major causes of pregnancy-related mortality and morbidity. This study aimed to determine the frequency of factor V Leiden (FVL) and prothrombin G20210A polymorphisms and measure the plasma levels of protein C (PC), protein S (PS) and antithrombin (AT) in pregnant women with VTE and healthy pregnant women. This prospective case-control study determined the frequencies of FVL G1691A and prothrombin G20210A polymorphisms and measured the plasma levels of PC, PS and AT in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Pregnancy-related venous thromboembolism. We found two studies that examined the impact of contraceptive use on the risk of venous thromboembolism (VTE) during pregnancy compared to non-users [29,30]. The results indicated that there was a 94% higher risk of VTE among contraceptive users (95% CI 1.49, 2.52).…”
Section: Maternal Morbiditymentioning
confidence: 99%
“…Pregnancy-related venous thromboembolism. We found two studies that examined the impact of contraceptive use on the risk of venous thromboembolism (VTE) during pregnancy compared to non-users [29,30]. The results indicated that there was a 94% higher risk of VTE among contraceptive users (95% CI 1.49, 2.52).…”
Section: Maternal Morbiditymentioning
confidence: 99%
“…Numerous investigations have posited that a reduction in the concentrations of AT, PC, and PS may contribute to an augmented predisposition to DVT [9]. Hence, the assessment of these coagulation inhibitor levels among gravid females employing oral contraceptives can impart valuable perspicacity into the hazard of DVT within this cohort.…”
Section: Introductionmentioning
confidence: 99%